ANALISIS PENGARUH PERTUMBUHAN PERUSAHAAN, KEBIJAKAN UTANG, COLLATERALIZABLE ASSETS, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2012-2014 - Loh Wenny Setiawati; Lusiana Yesisca (Jurnal Akuntansi, 2016)
Companies that issued shares to raise funds, must set aside some of the profits to be distributed as dividends. Dividend policy is a policy of how large distributions to the company's shareholders in proportion to the number of shares owned. Companies should establish a policy of dividend because the distribution of dividend will have an impact on corporate value as reflected in stock prices. This study uses multiple linear regression analysis which were processed using SPSS version 22. This study aimed to examine the effect on firm growth, debt policy, collateralizable assets, and firm size to dividend policy of the company. The sample used in this study were 105 companies listed in Indonesia Stock Exchange from the period 2012-2014. Empirically, it was found that the firm growth and firm size were affected to the dividend policy of the company, while the debt policy and collateralizable assets were not affected to the dividend policy of the company.